In Solidarity: Ma(r)king and Rescaling Solidarity Boundaries towards Migrants - Magazzini, Tina; Desille, Amandine (PARTECIPAZIONE E CONFLITTO, 2023)
The core idea for this Special Issue is to reflect upon the dynamics of participation both by individuals and by groups acting in solidarity with migrants in different contexts at the individual, local and transnational levels. Using the concept of "solidarities" to address the relation between persons who have experienced migration and persons who have not, and between people and institutions, enables research to escape the "us vs. them" dichotomy, extending the debate on deservingness to society as a whole. Moreover, with the development of crossborder volunteering and the diffusion of multi-scalar partnerships between subnational governments and civil society organisations, solidarities are rescaled, and encompass new forms beyond national welfare mechanisms. Bringing together a rich collection of empirical cases that ranges from the reception of the Rohingya refugees in the CoxBazar region of Bangladesh to border crossings along the Balkan route, from disaster solidarity in the Hanshin area in Japan to Ukrainian refugee reception in Italy, we explore acts of solidarity in different contexts as a way to try an make sense of when solidarity towards migrants is a political act, when it is about providing basic provisions subcontracted by the state to local or non-governmental actors, and when it is an act of defiance against the state.